PENATALAKSANAAN FISIOTERAPI PADA TRIGGER FINGER DENGAN ULTRASOUND DAN STRETCHING EXERCISE UNTUK MENINGKATKAN AKTIVITAS FUNGSIONAL - Ongebele, Gracia; Pombu, Novtiyas Maria (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2023)
Background: Trigger Finger or locked finger is a type of case that occurs in the tendon which functions to flex the fingers. Trigger finger can occur due to inflammation in the area of injury or swelling of the tendon sheath can also occur, which causes the tendon sheath to be unable to work according to its mechanism. This can be caused by many activities such as flexing the hand, making a fist or grasping which is easier, faster, and often experiences trigger finger. Objective: To find out the Physiotherapy Management of Trigger Finger Using Ultrasound and Stretching Exercises to Increase Functional Activities. Method: case study conducted on a 55 year old respondent who complained of pain in the right shoulder. Results: After receiving physiotherapy treatment using Ultrasound and Stretching Exercise for 6 therapy sessions which were evaluated using the wrist and hand disability index (WHDI), good results were found in increasing the patient's functional activity. In the first therapy the result was 28 (moderate dependence) after the sixth therapy the result was 6 (minimal/small dependence). Conclusion: by carrying out physiotherapy treatment using Ultrasound and Stretching Exercise 6 times, the result was an increase in functional activity.